Gut Barrier Function Is Improved in Infants Colonized by Bifidobacterium Longum Subsp. Infantis EVC001 (FS04-05-19). (13th June 2019) - Casaburi, Giorgio; Karav, Sercan; Frese, Steve; Henrick, Bethany
Abstract: Objectives: The gut epithelium is single-celled barrier that employs many different mechanisms that together provide the first line of defense to physically separate the gut epithelium from our gut microbiome. Notably, the epithelial barrier is protected by a mucin layer providing a physical barrier limiting pathogen access to the epithelial monolayer. We sought to assess how changes in the gut microbiome resulting from colonization by a single strain of Bifidobacterium longum subsp. infantis EVC001 could alter gut barrier function. Methods: Fecal samples from this trial were assessed for: (1) endotoxin (lipopolysaccharide) concentration; (2) functional contributions to the gut microbiome by shotgun metagenome sequencing; and (3) fecal glycan profiles by mass spectrometry to assess gut epithelial barrier integrity via breakdown of colonic mucin glycoproteins. Results: Colonization with Bifidobacterium, including B. infantis EVC001, showed a significant four-fold reduction in fecal endoxtoxin levels and reductions in fecal inflammatory markers ( P  < 0.05). Shotgun metagenomics identified LPS-producing Enterobacteriaceae as the most significant contributor of virulence factors in the infant gut metagenome. These bacteria (primarily E. coli and Klebsiella spp.) were also significantly correlated with both mucolytic bacteria (e.g., Bacteroides ) and the signatures of mucin breakdown, as assessed by mass spectrometric quantification of colonic mucin-derived glycans. Five different colonic-mucin specific glycans (3_1_1_0, 2_1_2_0, 2_1_1_1, 2_1_1_0, and 1_1_0_1) were significantly associated with microbiome composition ( P  < 0.05). Overall mucin glycans were inversely correlated with Bifidobacteriaceae abundance (Spearman's rho −0.66, FDR-corrected P value 0.04). Conclusions: Complex interactions between the degradation of gut barrier function ( e.g., mucin), the production of pro-inflammatory endotoxins, and the risk of infection by these bacteria coming in close contact with the gut epithelium suggest that B. infantis EVC001 can play a role in reducing these combined risks for neonates. Funding Sources: This work was funded by Evolve Biosystems, Inc.